2008
DOI: 10.1179/136217108x333327
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of SiC particle reinforced composite on aluminium surface by friction stir processing

Abstract: A feasibility investigation has been carried out of the formation of surface composite by uniformly distributing SiC particles 1?25 mm in size into a surface layer of an A 1050-H24 Al plate through friction stir processing (FSP). The SiC particle was filled into a groove cut on the Al plate, covered by an Al sheet 2 mm thick, and a rotating tool was penetrated from the cover sheet so that the probe tip reached a depth beyond the groove bottom. The effects of process parameters (rotation speed and travelling sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 69 publications
2
55
0
Order By: Relevance
“…These conditions produced the best results in terms of homogeneity of the particles inside the nugget zone for producing the SMMCs of the pure Al reinforced with SiC particles. 39,40) Double and triple passes were applied in order to improve the homogeneity of the reinforcement particle distribution. In the second pass, the tool was travelled along the same line as the first and third ones but in the opposite direction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions produced the best results in terms of homogeneity of the particles inside the nugget zone for producing the SMMCs of the pure Al reinforced with SiC particles. 39,40) Double and triple passes were applied in order to improve the homogeneity of the reinforcement particle distribution. In the second pass, the tool was travelled along the same line as the first and third ones but in the opposite direction.…”
Section: Methodsmentioning
confidence: 99%
“…29,32,33) It is considered that SMMCs are one of the latest applications of FSP. [34][35][36][37][38][39][40] The stirring action and frictional heat generated by the FSP tool can be used to distribute ceramic particles as reinforcement on the surface of light metals like aluminum and magnesium. [34][35][36][37][38][39][40] The present authors 39,40) succeeded in uniformly distributing SiC particles of 1.25 mm size in a surface layer of a few mm thickness on Al 1050-H24 plates to form surface composites by FSP.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its low density and low cost, SiC enhances an increase in the Young's modulus, hardness and tensile strength. However, these composites suffer from a great loss in ductility and toughness due to the undesirable reactions between SiC particles and aluminum, yielding Al 4 C 3 interfacial product, which limits their applications to a certain extent (Mahmoud et al, 2008). On the other hand, Titanium diboride (TiB 2 ) has distinct advantages over SiC because of its inertness to aluminum matrix (Shackelford and Alexander, 2001).…”
Section: Science Publicationsmentioning
confidence: 99%
“…2 Mahmoud et al fabricated AA1050/SiC SMMC, their results showed that the distribution of the SiC particles became more homogeneous with an increasing number of passes and with the combination of tool rotational speed and the processing speed resulted in the formation of defects, such as voids and tunnels in the FSP zone. 20 E. R. I. Mahmoud et al 20 also fabricated AA1050/SiC SMMC and assessed the effect of the tool pin size and profile. From their results, the wear rates of the samples produced with the flat surface tools were higher than that of the samples produced with the round-shaped tools and the samples produced with the square profile pin yielded a finer distribution of the SiC particles.…”
Section: Introductionmentioning
confidence: 99%
“…The welding process was carried out by rotating 1500 min -1 and by moving 200 mm/min. Under a constant friction force this involved four different shoulder diameters of (20,25,30 and 40) mm. During welding, temperature measurements were performed using a non-contact laser thermometer at various parts of the plates from the welding centre outwards.…”
Section: Introductionmentioning
confidence: 99%